Conjunctival ImpressionCytology (CIC) in Febrile Children inPediatrics Department of M. Djamil General Hospital, Padang - Marjis Marjis; Hafid Ardy (Indonesian Food and Nutrition Progress, 2003)
Febrile children due to infectious disease will suffer relative deficiency of vitamin A, due to increased ofvitamin A excretion via urine, non specific reaction to fever, and decreased food intake, thus absorption will also decrease. This study is to know the picture of conjunctival impression cytology (CIC) of febrile children. Method: Cases, Patients were hospitalized febrile children aged between 2-7 years old at the Pediatrics Department, M Djamil General Hospital, Padang, in a period of two months :March and April 2003. Patiens nutritional states were evaluated using Height, Weight, and Age parameters used in a standard formula to be compared to normal standard WHO tabel. CIC test were done according to Tseng method. Examinations were done on the first day of hospitalization. As controle group, 16 eyes of normal non febrile children were used. The significance of differences of Nutritional state and CIC picture were statically analyzed. Result: In febrile group the result of CIC examination was statistical significant. But nutritional state, frequency of febrile in a year and duration of the febrile weren't. Further study will be needed with a larger number of patients and longer duration offever. Conclusion: CIC examination of the conjunctiva is a simple test and have a good result to detect (relative) vitamin A deficiency in febrile patients.